Catalytic pyrolysis as a technology to dispose of herbal medicine waste - Lee, Younghyun; Kim, Soosan; Kim, Jisu; Shin, Gwy Am; Lee, Chang Gu; Jung, Seungho; Lee, Jechan (Catalysts, 2020)
The use of herbal medicine has increased tremendously over the last decades, generating a considerable amount of herbal medicine waste. Pyrolysis is a promising option to dispose of biomass and organic waste such as herbal medicine waste. Herein, an activated carbon-supported Pt catalyst (Pt/AC) and carbon dioxide (CO2) were applied to the pyrolysis of real herbal medicine waste to develop a thermal disposal method to prevent the formation of benzene derivatives that are harmful to the environment and human health. When using the Pt/AC catalyst in the pyrolysis of the herbal medicine waste at 500◦C, the generation of benzyl species was suppressed. This was likely because the Pt catalytic sites accelerate a free radical mechanism that is dominant in the thermal cracking of carbonaceous substances. However, the employment of CO2 (instead of typically used N2) as a pyrolysis medium for the herbal medicine waste pyrolysis did not decrease the concentrations of benzyl compounds contained in the pyrolytic products of the herbal medicine waste. This study might help develop a method to thermally dispose of agricultural biowaste, preventing the formation of harmful chemicals to the environment and human beings.
Keywords: Catalytic pyrolysis; CO2 utilization; Herbal medicine; Thermochemical process; Waste disposal